THEOLOGICAL DEBATES ON ASH‘ARIYYA TENETS; AN ANALYSIS OF THE FATH AL-MAGID BY NAWAWI AL-BANTANI (1814-1897) - Entol Zaenal Muttaqin (Al Qalam, 2017)
There are some differences in defining Islamic theology since the era of prophet Muhammad. Some of them emerged from political aspects, and some of them are not. The two prominent ideologies in Islamic theology are Ash’ariyya derived from Sunni, and Mu’tazilla from Syi’a. One of significant scholars in 19 century, Nawawi al-bantani, wrote many books in wide Islamic studies, one of them is Fath al-Magid in theology. Many scholars wrote and designated themselves to a particular group. In contrary, although Nawawi al-Bantani confessed himself as Sunni scholar, yet in some of his writing including Fath al-Magid, he opposed Ash’ariyya and defended Mu’tazila. To some extent, this manner will come up into a unique scholarship tradition for some scholars, indeed, this research aimed to investigate this behavior in final words this paper concluded that Nawawi distanced himself from Ash’ari when he stated that God’s essence and His attributes are inseparable and thereby preserve the oneness of God. He adopted both Ash’ari’s concept, that the Qur’an is not created (ghayr makhluq and it is qadim) and Mu’tazila’s concept, that the Qur’an is created (makhluq and it is hadith). According to Nawawi, the Qur’an is created when it refers to the text and the sound, but uncreated when it refers to the underlying meaning of each verse, even if this contradicts the concept of free will that Nawawi adopted. For his last explanation, pertaining to the concept of prophecy, ru’ya and shafa’a, Nawawi provided a very general explanation, neglecting to elaborate on some important issues relating to the concept of prophecy. it is obvious that Fath al-Magid, with its different interpretation of Ash’ari’s work, meant it was similar to other Sunni theological works that aimed to modify Ash’ari’s original doctrine.